Structure Community and Distribution of Benthic Foraminifera in the Waters of Bagan Tanjungbalai Village Asahan Regency North Sumatera Province - Pohan, Rizal Suardiman; Rifardi, Rifardi; Efriyeldi, Efriyeldi (Journal of Coastal and Ocean Sciences, 2020)
This research was conducted in March 2019 in the waters of Bagan Tanjungbalai Village Asahan Regency North Sumatera Province. The purpose of the study were to analyze the community  structure and distribution of benthic foraminifera. Determination of the research was purposive sampling of 4 station with 3 sampling points where the distance each sampling point was 50 meters wich were based on the initial sampling point. In the study area were found 24 species of foraminifera.  The study showed that composition of sediment organic matter involved 4.97 - 15.26%, while the abundance of benthic foraminifera was between 13690 - 28571 ind/m2. Defferences of the abundance of benthic foraminifera at each station obtained a significant value of 0.01 or p < 0.05, which means a difference the abundance of  benthic foraminifera beetwen stations,but not significant. While the relative abundance between sampling is only 0.15-21.00%, while the relative sedimentation rate between sampling is 15.38 - 33.02%.